Cortisol and physical performance in older populations: findings from the International Mobility In Aging Study (IMIAS) - Sousa, Ana Carolina Patrício de Albuquerque (2021)
Objective: To compare diurnal cortisol profiles across samples of older adults from diverse populations and to examine if differences in circadian cortisol secretion are associated with poor physical performance (SPPB<9). Methods: Data were collected during the baseline survey of the International Mobility in Aging Study conducted in 2012 in Kingston (Canada), Saint-Hyacinthe (Canada), Tirana (Albania) and Manizales (Colombia). Salivary cortisol was collected from a subsample of 309 participants instructed to collect saliva on two consecutive days, and 5 different intervals each day: upon awakening (M1), 30 min (M2) and 60 min after awakening, at 15:00 h and before bedtime (E). Cortisol was analyzed using enzyme immunoassay kits. Physical performance was measured by the Short Physical Performance Battery (SPPB). Mixed linear models were fit to assess the associations between cortisol diurnal output and physical performance, adjusting for potential confounders. Results: Kingston, Saint-Hyacinthe and Tirana residents had significantly higher cortisol values than their Manizales counterparts, with the population from Tirana showing the highest levels. Attenuated morning cortisol peak (M2) (p = 0.025), higher cortisol bed time (E) (p = 0.005), and lower M2/E ratio (p < 0.001) were found among those with SPPB<9 compared with those with good physical performance (SPPB 9). These results were not altered after adjustment by potential confounders. Conclusion: Cortisol profiles varied across four diverse populations of older adults. Circadian cortisol secretion is associated with physical performance as an attenuated morning response and higher bed time values were observed in older adults with SPPB < 9